Joint User Scheduling and Beam Selection for Maritime Large-scale Antenna Systems. Issue 6 (April 2019) - Lu, Xiaochun; Sun, Qiang; Xu, Chen; Wu, Yezeng
Abstract: Since the overall distribution of users in the sea area is sparse, it will appear densely in a local angle domain. Specifically, the 3D massive MIMO antenna system are established, which are with the ability to distinguish users in the same horizontal direction as well as vertical direction. According to this, a joint user scheduling and beam selection scheme based on the automatic identification system (AIS) is proposed to solve the problems that of the interference cancellation for the users in the angle domain. In particular, the proposed scheme divides the beam according to the users' location information. Furthermore, we select the user with the highest priority in the beam to form a set of the users in serving, in the meanwhile, the greedy algorithm is used to schedule the user combination to achieve the greatest sum rate. By means of the numerical results, it is shown that the proposed scheme can be used to schedule and serve users in the case of crowded angle domain, and the scheme can obtain near-optimal sum rate.